PERAN SERTA MASYARAKAT DALAM PENGELOLAAN SAMPAH SEBAGAI KUNCI KEBERHASILAN DALAM MENGELOLA SAMPAH - Ni Made Armadi (Sekolah Tinggi Ilmu Sosial Politik Wira Bhakti, 2021)
The waste problem is a problem that must be faced by society and has become a global problem. The community is at the forefront of waste management. The purpose of this study was to determine the role of the community in waste management as the key to successfully managing waste. The research method used was literature study and interviews. The result of this research was that the community participation in Denpasar City was quite effective in waste management activities through composting and 3R (reuse, reduce and recycle). Denpasar Government provided incentives for integrated waste management as a stimulus to improve community‘s active involvement.